Enhancing Small Culinary Business Competitiveness: A Business Model Canvas Analysis of a Boba Drink UMKM: Meningkatkan Daya Saing Usaha Kuliner Kecil: Analisis Kanvas Model Bisnis UMKM Minuman Boba - Haryani, Dwi Septi; Saputra, Eka Kurnia; Abriyoso, Octojaya; Yeo, Cecilia; Ardian, Novra (Indonesian Journal of Law and Economics Review, 2023)
This study focuses on a culinary business in Tanjungpinang City, investigating the application of a business model canvas for UMKM Fortunate Boba, renowned for its signature boba-topped cold beverages. With the aim to enhance competitiveness amidst similar ventures, qualitative analysis employing the business canvas model approach was conducted through interviews with UMKM Fortunate Boba's owner. The results of the Business Model Canvas (BMC) analysis unveil strategic utilization of social media platforms like Facebook and TikTok, e-money transaction systems, and collaborations with delivery services such as Go-Jek and Maxim to streamline order deliveries. This research underscores the practical implementation of a business model canvas to optimize the operations of UMKM Fortunate Boba, highlighting key strategies for thriving in the competitive culinary market. Highlight: UMKM Enhancement: This study examines the application of a business model canvas for UMKM Fortunate Boba, specializing in boba-topped cold beverages, to enhance competitiveness in a competitive culinary market. Qualitative Approach: Through qualitative analysis and owner interviews, the study employs the business canvas model to uncover strategic approaches, including social media utilization, e-money transactions, and delivery collaborations. Operational Optimization: The research underscores the practical implementation of the business model canvas, providing valuable insights into strategic adaptations that enable UMKM Fortunate Boba to thrive amidst competition and streamline operational efficiency. Keyword: Culinary Business, Business Model Canvas, Competitiveness, Qualitative Analysis, Strategic Optimization